Bromfenac ophthalmic solution 0.09% as an adjunctive therapy to topical steroids after cataract surgery in pseudoexfoliation syndrome. Issue 8 (August 2016) - Coassin, Marco; Iovieno, Alfonso; Soldani, Anna; Cavuto, Silvio; Cimino, Luca; Sartori, Antonio; Formisano, Debora; Fontana, Luigi
Abstract : Purpose : To study with laser flare photometry the antiinflammatory effect of bromfenac added to a topical steroid versus a topical steroid alone in patients with pseudoexfoliation (PXF) syndrome after cataract surgery. Setting : Ophthalmology Unit, Santa Maria Nuova Hospital, Reggio Emilia, Italy. Design : Randomized clinical trial. Methods : Patients with cataract and clinical signs of PXF were randomized to dexamethasone 0.1% and tobramycin 0.3% ophthalmic solution (Group 1) or with the adjunct of bromfenac ophthalmic solution 0.09% (Group 2). All patients were examined on the day of surgery (baseline) and postoperatively at 1, 3, 7, and 30 days. Laser flare photometry was used to quantify anterior chamber inflammation and optical coherence tomography to measure macular thickness. Results : Sixty‐two patients were included. Postoperatively, the mean flare was 31% lower in Group 2 than in Group 1 at 3 days (11.92 ph/msec ± 8.14 [SD] versus 17.13 ± 9.03 ph/msec; P = .025) and 43% lower at 7 days (10.77 ± 6.17 ph/msec versus 18.72 ± 12.37 ph/msec; P = .003). There were no significant differences in postoperative visual acuity, symptoms, or ocular pain between groups. The mean macular thickness 1 month after surgery was increased in Group 1 but not Group 2; the difference between groups was significant at 4 weeks ( P = .03). The incidence of intraretinal cysts was higher in Group 1 (n = 4) than in Group 2 (n = 0). Conclusion : The addition of bromfenac to topical steroids after cataract surgery in eyes with PXF was associated with greater reductions in inflammation than steroids alone. Financial Disclosure : None of the authors has a financial or proprietary interest in any material or method mentioned.